Frozen shoulder after COVID-19 vaccination - Clevio Desouza; Vijay Shetty (Journal of Orthopaedic Reports, 2024)
Introduction: This study addresses the current gap in the literature regarding frozen shoulder and Shoulder Injury Related to Vaccine Administration (SIRVA) following COVID-19 immunization. The primary objectives are to describe the demographic characteristics of patients who developed frozen shoulder as a result of COVID-19 vaccination and to identify commonalities with previous findings. Ultimately, this study aims to enhance healthcare providers' awareness of these conditions and provide insights for potential prevention strategies. Materials and methods: This retrospective study analysed a cohort of 80 patients (56 females and 24 males) with an average age of 53 years (±8 years). These patients sought medical care in the orthopaedic outpatient department due to shoulder stiffness and pain following COVID-19 vaccination between July 1, 2021, and July 31, 2022. Results: Radiographs of all 80 patients showed no abnormalities, and they were diagnosed with frozen shoulder. Among these patients, 20 had pre-existing medical conditions (4 with hypothyroidism, 12 with diabetes mellitus, and 4 with hypertension) at the time of presentation. Symptoms manifested immediately after vaccination in 48 patients, at 48 hours in 8 patients, and at 10 days in 24 patients. The average pain level, as assessed using the Visual Analog Scale (VAS), was 6.4 (±1.2), and both active and passive range of motion was restricted in all patients upon presentation. Conclusion: Healthcare professionals specializing in musculoskeletal issues should be mindful of the possibility of frozen shoulder occurring after COVID-19 vaccination in patients presenting with painful shoulder stiffness. Early recognition and treatment of this condition are essential for effective patient care.